A Two-Loop Control Method for Shaking Table Tests Combining Model Reference Adaptive Control and Three-Variable Control - Yachun, Tsai; Peng, Pan; Dongbin, Zhang; Yi, Zeng (Frontiers in Built Environment, 2018)
Shaking table tests are the most direct experimental way to evaluate structural performance in earthquake engineering. Because of the complexity of the control systems and the influence of specimen behaviour, it is difficult for a conventional controller, whose parameters are fixed, to achieve accurate tracking performance for different reference input signals under different payloads. In this paper, a two-loop control method is proposed by combining three-variable control and model reference adaptive control based on Lyapunov stability theory. The proposed control method can adjust the time-domain drive signal adaptively to improve the tracking accuracy and the robustness to specimen uncertainties. Numerical simulations of a small-scale shaking table are used to verify the effectiveness, and the performance of the controller is compared with that of the conventional three-variable control controller. The simulation results demonstrate that the proposed two loop control method provides better performance in both the time and frequency domains.